Fuzzy active vibration control for lathe machine - Muhamad Faisal Ezuarie , Draman (2010)
This project report deals with development of the control system for the conventional lathe machine. Vibration during turning process caused chatter in surface product and affects the outcome of products. The control system used to suppress vibration a chatter using machining process. Dynamic and mathematically model had derived from the two degree of freedom (2-DOF) for the cutting tool. Control system used in project a passive system and active system. The passive system used to show the instability of system. For active system that had been introduces two type of controller such as typically technique proportional-integral-derivative (PID) and Fuzzy Logic Control (FLC). To complete the active system, linear actuator had been used. The simulation had been run using MATLAB/SIMULINK® software. Comparative study had been done between passive and active control system. From comparative study, Fuzzy PID showed an effectiveness result that suppresses vibration during machining process. Fuzzy PID produced small error nether than typically PID and passive system. For the conclusion, Fuzzy PID control is superior robust, stable and accurate controller compare the PID control.